Communication from the executive of the Commonwealth, transmitting the nominations of Benjamin S. Ewell, John A. Campbell and William Smith, as colonels of volunteers (LLMC-digital (Series), 1861)
Governor John Letcher's June 26, 1861 letter of nominations of Benjamin S. Ewell, John A. Campbell, and William Smith to various commissions in the volunteer regiments.